MicroRNA-92a promotes proliferation and invasiveness of gastric cancer cell by targeting FOXO1 gene - Yu, Jiawei; Ni, Qingfeng; Zhang, Shu; Hua, Ruheng; Tao, Ran; Tang, Chong; Feng, Shichun (Cellular and Molecular Biology, 2020)
The aim of this study is to investigate the effect of miRNA-92a on GC cell proliferation, migration and invasiveness, and the mechanism(s) involved. Four GC cell lines (SGC-7901, BGC-823, MKN45 and HGC-27) and normal human gastric epithelial cells (GES1) were used in this study. MicroRNA-92a mimics or inhibitor were transfected into the cells. The results of transfection were assessed using real-time quantitative polymerase chain reaction (qRT-PCR). Cell proliferation, migration, invasiveness and apoptosis were determined using cell counting kit 8 (CCK-8), scratch test, Transwell invasion assay, and flow cytometric analysis, respectively. The protein target of miRNA-92a was predicted using Bioinformatics. The expression of FOXO1 protein was measured using Western blotting. The expression of miRNA-92a was significantly upregulated in GC cells, relative to normal gastric epithelial cells (p < 0.05). Overexpression of miRNA-92a significantly promoted the proliferation, migration and invasiveness of GC cells, but significantly inhibited their apoptosis (p < 0.05). MicroRNA-92a directly targeted FOXO1 gene, and significantly reduced its protein expression. Overexpression of miRNA-92a promotes the proliferation, migration and invasiveness of GC cells, and plays a role similar to that of oncogene. It directly targets FOXO1 gene by inhibiting its protein expression.